Economic Characteristics of the Population in the Prefecture of Cyclades - Pafili, Efrosini (SPOUDAI Journal of Economics and Business, 2008)
The aim of the present study is the evaluation of the economic development in the Prefecture of Cyclades. Using indicators of the economic activity, we assess the participation of the population in productivity, during a period of thirty years (1971-2001), studying the workforce of this Prefecture in combination with: The sector of the production The professional teams The position at work JEL Classification: A12